Distinguishing collaboration from related elements of crime - O. V. Pletnov; Ye. V. Kovalenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the distinction between the corpus delicti of crimes under Article 111-1 of the Criminal Code of Ukraine “Collaboration” and related crimes. Scientific articles by researchers who studied who have studied the objective and subjective features of collaboration have been analysed. It is stated that collaboration differs from high treason by the nature of the acts constituting the objective element of the crime, the time of the crime and the subject of the crime. The collaboration is distinguished from aiding and abetting the aggressor State by the subject of collaboration.The set of actions that make up the objective side of the specified crimes also has differences. The difference between the creation of illegal paramilitary formations and collaborative activities lies in the object of the crime. In addition, the crime provided for in Part 7 of Article 111-1 of the Criminal Code of Ukraine is committed in the conditions of the Ukrainian territory occupation as a result of the invasion of the aggressor state troops. The collaborative activity must be distinguished from the crime provided for in Article 436-2 of the Criminal Code of Ukraine “Justification, recognition as legitimate, denial of the armed aggression of the russian federation against Ukraine, glorification of its participants”. The differences are in the object of the crime. In addition, collaboration can only be carried out in the occupied territory.It is proposed to make changes to the Criminal Code of Ukraine. In particular, it is proposed to define the concept of subversive activity, which is used in Article 111 of the Criminal Code of Ukraine. It is necessary to specify the list of actions that can be considered as assisting the enemy in subversive activities. Establish clear distinctions between collaborative activities and assisting the enemy in subversive activities. It is necessary to solve other problematic issues of qualification of violations of the legislation of Ukraine under Article 111-1 of the Criminal Code of Ukraine or other articles of the Code containing similar offenses.